2021
DOI: 10.1007/s00170-020-06450-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of force displacement curves in blanking—feature engineering beyond defect detection

Abstract: With the current tendency of mass production towards customer-oriented serial production, blanking processes are facing new challenges. They require an increase in knowledge about faulty process conditions and their influence on the quality of a component as well as an instruction for a target-oriented adaptation of the process. The aim of this study is therefore to identify property deviations based on force-displacement curves and to establish correlations between the quality of the component and features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In this work we focus on the rounding of the cutting edge radii by abrasive wear. Hambli, Klingenberg and Singh as well as Kubik et al showed in their work that exactly this abrasive wear is the most common cause of wear in blanking and has a significant influence on the quality of the component (Hambli, 2001;Klingenberg & Singh, 2004;Kubik et al 2021).…”
Section: Data-driven Monitoring Of Blanking Processesmentioning
confidence: 94%
See 1 more Smart Citation
“…In this work we focus on the rounding of the cutting edge radii by abrasive wear. Hambli, Klingenberg and Singh as well as Kubik et al showed in their work that exactly this abrasive wear is the most common cause of wear in blanking and has a significant influence on the quality of the component (Hambli, 2001;Klingenberg & Singh, 2004;Kubik et al 2021).…”
Section: Data-driven Monitoring Of Blanking Processesmentioning
confidence: 94%
“…According to Li, features can be extracted either from the time domain, the frequency domain or the time-frequency domain (Wang & Gao, 2006 show in their studies that engineering feature from the time domain represent effective parameters for describing process conditions during blanking (see Fig. 8) (Hoppe et al 2019;Kubik et al 2021). Therefore, the force signal is initially divided into three phases and characteristic points which define the start and end points as well as extrema during each phase are identified.…”
Section: Data Transformationmentioning
confidence: 99%
“…Considering the maximum force, the most suitable deep drawing process was chosen on the Ecoinvent database (650 kN deep drawing process). Blanking maximum force was calculated as follows [39]:…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…acceleration [18], force [19], acoustic emission [20]). In addition, different approaches for expert systems [21], feature engineering approaches [5,11,12,22] or by artificial neural networks [23,24] were made to predict the process quality. To our best knowledge, the current state-of-the-art of inline measurement systems for quality monitoring of the cutting surface parameters is only established via the correlation with indirect measured parameters or engineered features.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.2Selection of process parameters that are most likely to influence the cutting surface parameters[22,25] …”
mentioning
confidence: 99%